2000
DOI: 10.1073/pnas.100104597
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in memory and motor performance in synaptotagmin IV mutant mice

Abstract: Synaptotagmin (Syt) IV is a synaptic vesicle protein. Syt IV expression is induced in the rat hippocampus after systemic kainic acid treatment. To examine the functional role of this protein in vivo, we derived Syt IV null [Syt IV(؊͞؊)] mutant mice. Studies with the rotorod revealed that the Syt IV mutants have impaired motor coordination, a result consistent with constitutive Syt IV expression in the cerebellum. Because Syt IV is thought to modulate synaptic function, we also have examined Syt IV mutant mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
96
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 55 publications
4
96
1
Order By: Relevance
“…Our data are consistent with a role for defective endocytosis as an underlying mechanism in HD (Trushina et al, 2006). Importantly, mouse knock-outs of synaptic and/or htt-interacting proteins such as HIP1 (Ferguson et al, 2000;Metzler et al, 2007;Nystuen et al, 2007) often have neurological phenotypes that may be relevant to HD pathogenesis.…”
supporting
confidence: 87%
“…Our data are consistent with a role for defective endocytosis as an underlying mechanism in HD (Trushina et al, 2006). Importantly, mouse knock-outs of synaptic and/or htt-interacting proteins such as HIP1 (Ferguson et al, 2000;Metzler et al, 2007;Nystuen et al, 2007) often have neurological phenotypes that may be relevant to HD pathogenesis.…”
supporting
confidence: 87%
“…The predominant expression of Syt IV in astrocytes and its absence from nerve terminals is of great interest because hippocampal-based memory formation has been reported to be impaired in syt4 knockout mice (49). Because glutamate released from astrocytes has been shown to activate extrasynaptic Nmethyl-D-aspartate receptors of hippocampal pyramidal neurons (56) it will be extremely interesting to determine whether this gliotransmission pathway is critical for the induction of processes such as long-term potentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the corresponding preservation of the glutamate receptor subunit GluR1, synaptic vesicle markers, and basal levels of active ERK. Note that GluR1 (Schmitt et al, 2004), the synaptic vesicle protein synaptotagmin IV (Ferguson et al, 2000), and the ERK/ MAPK pathway within hippocampal neurons (Shalin et al, 2004) have been shown to play important roles in memory functions, including fear conditioning. The results described here show that indirect enhancement of endocannabinoid responses protects against excitotoxic hippocampal damage and preserves mechanisms necessary for memory encoding.…”
Section: Discussionmentioning
confidence: 99%